Implementation of the Islamic Input in Orthopaedics (Triple IO) undergraduate medical curricula & practice. IIUM’s experience (2002-2014) - Sharifudin, Mohd Ariff; Ayeop, Mohd Adham Shah; Che Ahmad, Aminudin (2015)
The secularization of the modern fields of knowledge has lead to deprivation of religious and spiritual considerations, particularly in the current medical curriculum. In the past, the heavy medical curriculum has been blamed as a major contributing factor of production of ‘disease-oriented’ rather than ‘patient-oriented’ medical practitioners. Undergraduate students are very much unprepared to integrate the Islamic knowledge acquired during school-going years into the hectic life and specific conditions that they will encounter in the real clinical settings. There is a great need to reform the current education system to produce critical-minded medical practitioners, especially from the various aspects of the Islamic perspective. In IIUM, the teaching of medicine is augmented by series of relevant lectures and programs in line with the University’s Islamization of Human Knowledge agenda. The Department of Orthopaedics, Traumatology and Rehabilitation of IIUM has taken a step ahead by introducing the Islamic Input in Orthopaedics (Triple IO) Module since 2002. Since its implementation, various obstacles have been faced and many improvements have been made. After more than a decade, we would like to share our experience in conducting the program and how to improve it further to cope with future challenges.